2015
DOI: 10.4028/www.scientific.net/amm.725-726.1463
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Solutions of Power Supply in North Regions

Abstract: This article contains information about power economic estimation of power complexes creation based on renewable energy located in north regions with decentralized electric supply, where in the main electricity is produced by diesel power plants. Problems of using diesel power plants is measured; investigation of introducing wind-diesel power complexes is shown. Article contains information about power economic estimation, which allows to find out optimized solution to problem of choosing optimized energy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Our studies on the assessment of economic efficiency in Tiksi (Sakha-Yakutia) [16] showed that the developed method allows the selection of the most optimal option for implementing a decentralized generation project for renewable energy and reduces the cost of electricity production, reducing regional subsidies, increasing the investment attractiveness of the project, reducing costs diesel fuel and reducing its volume, reducing CO2 emissions.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies on the assessment of economic efficiency in Tiksi (Sakha-Yakutia) [16] showed that the developed method allows the selection of the most optimal option for implementing a decentralized generation project for renewable energy and reduces the cost of electricity production, reducing regional subsidies, increasing the investment attractiveness of the project, reducing costs diesel fuel and reducing its volume, reducing CO2 emissions.…”
Section: Resultsmentioning
confidence: 99%
“…At present, there is a tendency to install wind power plants on the Northern coasts of Europe and America, demonstrating the prospects for the effective use of high-power wind power plants [1]. Indeed, high wind energy potential characterizes the Far North and the Arctic regions, and the renewable wind energy resources of the Northern countries significantly exceed the capabilities of traditional hydrocarbon sources [2].…”
Section: Introductionmentioning
confidence: 99%
“…the table based on the data from[23] 2. the share of the power consumption of the protection system from the rated power of the wind generator.…”
mentioning
confidence: 99%
“…Centralized and non-renewable systems, namely large-scale facilities using fossil fuels such as oil and coke, are environmentally unsustainable because they rely on resource depletion. Furthermore, these exhaustible resources result in high greenhouse gas emissions (CO2 emissions) from several processes during their life cycle that contributes to global warming [1][2][3]. As a result, they lead to other pollution problems during their extraction and transport processes.…”
Section: Introductionmentioning
confidence: 99%